Trends in Russian statistics on the incidence of young cohorts - T.V. Leushina (Интеллект. Инновации. Инвестиции, 2019)
The demographic aging of citizens of the Russian Federation, and, as a consequence, the increase in the demographic burden of older people on the working-age population, in recent decades has come to the forefront of the existing socio-economic problems. In this regard, the study of tendencies in the change in the number and state of health of the younger generation – children and adolescents, those young population cohorts, who will determine the future prospects for the development of Russia is relevant. In the near future, they will occupy leading positions in the social sphere, politics and economics. The most important demographic processes belong to the category of stochastic (probabilistic) phenomena and traditionally are the subject of application of the methodology of statistical sciences, in particular, they are such branches as population statistics and social statistics. Statistical estimation methods allow to reliably and adequately characterize not only the current situation in the demographic situation of a country and regions, but also with a high degree of probability, with a sufficient number of mass observations, to model trends for the short and medium term. The aim of the study was a structuraldynamic statistical analysis of the overall incidence of children and adolescents in the Russian Federation, as well as the incidence of new infections, drug addiction and HIV infections, as socially dangerous diseases. In the conducted study, the structure of the results of preventive examinations of children in the Russian Federation was evaluated, which made it possible to identify the growth trends of certain diseases of these age categories. The chain and baseline morbidity rates of children with neoplasms in long-term dynamics were calculated. The absolute and relative incidence rates of adolescent HIV infection are calculated. Statistically estimated dynamics of the incidence of adolescent drug addiction. The trend was statistically estimated and statistical modeling and forecasting for the medium term was carried out using the method of analytical alignment (trend equation) of the incidence of malignant children in the Russian Federation based on official publications of the Federal State Statistics Service. Using the autoregression-moving average method, we constructed an adequate trend model and predicted the overall incidence rate of children aged 0–14 years, which made it possible to obtain predictable values for a medium term with a high degree of probability.